2007
DOI: 10.1080/00224490701580923
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' Sexual Scripts: Schematic Representations of Consensual and Nonconsensual Heterosexual Interactions

Abstract: The characteristic features of adolescents' sexual scripts were explored in 400 tenth and eleventh graders from Berlin, Germany. Participants rated the prototypical elements of three scripts for heterosexual interactions: (1) the prototypical script for the first consensual sexual intercourse with a new partner as pertaining to adolescents in general (general script); (2) the prototypical script for the first consensual sexual intercourse with a new partner as pertaining to themselves personally (individual sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 39 publications
3
29
0
1
Order By: Relevance
“…We know, for example, how people believe a first date progresses (Bartoli and Clark 2006;Frieze 1989, 1993), how individuals attempt to secure a date (Pryor and Merluzzi 1985), adolescents' scripts for sexual encounters (Krahé et al 2007), scripts relating to sexual intent (Lenton and Bryan 2005), as well as what happens when a relationship ends (Battaglia et al 1998;Honeycutt et al 1992). Results from these studies have allowed investigators to determine that generally shared scripts exist for these relationship events.…”
Section: Understanding Mental Representations Of Relationshipsmentioning
confidence: 95%
“…We know, for example, how people believe a first date progresses (Bartoli and Clark 2006;Frieze 1989, 1993), how individuals attempt to secure a date (Pryor and Merluzzi 1985), adolescents' scripts for sexual encounters (Krahé et al 2007), scripts relating to sexual intent (Lenton and Bryan 2005), as well as what happens when a relationship ends (Battaglia et al 1998;Honeycutt et al 1992). Results from these studies have allowed investigators to determine that generally shared scripts exist for these relationship events.…”
Section: Understanding Mental Representations Of Relationshipsmentioning
confidence: 95%
“…Then they depart, never to see each other again. (Female, 18 years old) Subsequent research showed the key features of rape scripts are the assailant's use of physical violence and the victim's resistance (e.g., Krahé et al 2007;Littleton and Axsom 2003), as well as negative psychological consequences for the victim (e.g., Littleton et al 2007). This is often called the real rape script (e.g., Horvath and Brown 2009).…”
Section: Rape Scriptsmentioning
confidence: 98%
“…For the present analysis, only the risk elements of the scripts will be considered. A full analysis of the scripts as a whole including all categories is reported by Krahé, Bieneck, and Scheinberger-Olwig (2006).…”
Section: Measures and Proceduresmentioning
confidence: 99%